(untitled) (Estudios Humanísticos. Filología, 1994)
There are two reasons why there is interest in Malinowski’s style. First, Malinowski was a principal inventor of the discipline of modern fieldwork and ethnography. Second, Malinowski is a man of many puzzles and contradictions. Malinowski ventured in the Argonauts of the Western Pacific, what became his characteristic style: a journey through the life cycle of an institution, led by a confident, always-present narrator and ethnologist. Our stylisic exploration is devoted to seeing the unity beneath puzzles, and once finding the patterns not immediately obvious, opening up new questions and further explorations.